1998
DOI: 10.1046/j.1365-2958.1998.00856.x
|View full text |Cite
|
Sign up to set email alerts
|

The telomeres of Streptomyces chromosomes contain conserved palindromic sequences with potential to form complex secondary structures

Abstract: SummaryThe chromosomes of the Gram-positive soil bacteria Streptomyces are linear DNA molecules, usually of about 8 Mb, containing a centrally located origin of replication and covalently bound terminal proteins (which are presumably involved in the completion of replication of the telomeres). The ends of the chromosomes contain inverted repeats of variable lengths. The terminal segments of five Streptomyces chromosomes and plasmids were cloned and sequenced. The sequences showed a high degree of conservation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
119
0
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 108 publications
(125 citation statements)
references
References 47 publications
5
119
0
1
Order By: Relevance
“…24,25) Fischer et al 26) reported that homologous recombination of two sigma factor-like ORFs caused chromosomal arm replacement in S. ambofaciens, which generated unusually long TIRs in the mutants. We also found that in S. griseus mutant MM9, homologous recombination between two similar lipoprotein-like ORFs caused chromosomal arm replacement and generated 450-kb TIRs in place of the original 24-kb TIRs.…”
Section: Discussionmentioning
confidence: 99%
“…24,25) Fischer et al 26) reported that homologous recombination of two sigma factor-like ORFs caused chromosomal arm replacement in S. ambofaciens, which generated unusually long TIRs in the mutants. We also found that in S. griseus mutant MM9, homologous recombination between two similar lipoprotein-like ORFs caused chromosomal arm replacement and generated 450-kb TIRs in place of the original 24-kb TIRs.…”
Section: Discussionmentioning
confidence: 99%
“…Two copies of the motif GCTXCGC were found in each terminus and it was already assumed earlier that these structures are essential for replication (Kalkus et al, 1998;Shimizu et al, 2001). Essentially the same central motif with the potential to form a stable single C-residue loop close to the sheared T : C pairing was found in the linear Streptomyces plasmids pSCL1 (Wu & Roy, 1993), pSLA2 (Hirochika et al, 1984) and SLP2 , as well as in the terminal segments of several linear Streptomyces chromosomes (Huang et al, 1998). In pSLA2 these structures were shown to be essential for replication and propagation of linearity (Qin & Cohen, 1998).…”
Section: Discussionmentioning
confidence: 70%
“…However, in p1CP-J the palindrome of position 12-34 is imperfect because of a mismatch at position 14. Both palindromic structures contain the central motif GCTXCGC, already obtained for other plasmid termini of rhodococci (Kalkus et al, 1998;Shimizu et al, 2001) and streptomycetes (Bey et al, 2000;Huang et al, 1998). Several other regions of striking similarity were identified (alignment positions 1-2, 5-7 and 49-62).…”
Section: +Sds +Sdsmentioning
confidence: 60%
See 1 more Smart Citation
“…13 These two features proved to be conserved in most of linear plasmids and chromosomes in actinobacteria. Cloning and sequencing of the terminal fragments revealed that the telomere sequence of SCP1 could not form a Y-shaped foldback structure, 14 a feature conserved in most Streptomyces linear replicons, 15 which may function in terminal replication. 16 Figure 2 The gross structures of the linear plasmids, SCP1 and pSLA2-L (a), and possible secondary telomere structures deduced from their sequences (b).…”
Section: Scp1 In Streptomyces Coelicolor Isolation and Characterizatimentioning
confidence: 99%